DAMPAK IMPLEMENTASI FORMULA UPAH MINIMUM SESUAI PERATURAN PEMERINTAH NOMOR 78 TAHUN 2015 TENTANG PENGUPAHAN TERHADAP KESEJAHTERAAN PEKERJA DI KABUPATEN BEKASI. - Timbul Handriyanto; Mahayoni Mahayoni (President University, 2018)
The Constitution states that every citizen has the right to work and a decent living for humanity, reinforced by the Manpower Act that every worker/laborer has the right to earn an income that fulfills a decent living for humanity. In achieving this goal, the state establishes a